Dampak Eksekusi Rumah Tinggal Terhadap Kelanjutan Pendidikan Anak Sekolah Dasar - Karmila P. Lamadang; Pupung Puspa Ardini; Ali Kaku; Lukman A.R. Laliyo (PEDAGOGIKA, 2020)
This study aims to determine the impact on elementary school children after the eviction in Tanjung Sari, Karaton, Luwuk Subdistrict, Banggai District, Indonesia. The study was conducted for three months, from February to June 2018. The research subjects were the community, especially children who were sitting in the elementary school along with parents of students at Tanjung Sari. Procedure This research is this research using procedures with stages including the following: planning, observation and implementation stages. In this study using qualitative and quantitative analysis techniques obtained through respondents' statements contained in the questionnaire data, and then to check the accuracy of the data is also carried out interviews, observation and documentation. While in describing the data obtained quantitatively used descriptive statistics, this was done in this study to obtain the correct information. Furthermore, in data processing there are two steps used, Data Selection and Classification The steps taken are a) checking whether all respondents; b) check all questions in the questionnaire to ensure answers according to the instructions given; c) check whether the collected data is suitable for processing. Then giving the score weight for each alternative answer in scoring is used Likert scale which is one way to determine the score. This technique is used to get the tendency of the scores given by respondents on each item of the question according to the criteria or benchmarks used. Based on the results of research conducted that the impact of residential execution on the continuity of education in elementary school age children in Tanjung Sari, Kelurahan Karwen, Luwuk Subdistrict, Banggai Regency has a very strong impact on the continuity of education in elementary school children in Tanjung Sari, Karaton, Luwuk Subdistrict, Banggai District.